Collectivism, face concern and Chinese-style lurking among university students: the moderating role of trait mindfulness - Hu, Bing; Zhu, Yi; Liu, Chao; Zheng, Shanshan; Zhao, Ziying; Bao, Ruxiang (Frontiers in Psychology, 2024)
This study explores the unique antecedents and mechanisms of "Chinese-style lurking" on WeChat among university students in a cultural context of collectivism and face concern, and investigates the moderating role of trait mindfulness. The Stress-Strain-Outcome (SSO) theory and mindfulness buffering theory were utilized to construct a structural equation model. The model was validated with data from 1453 valid online surveys analyzed using SmartPLS 4.0. Results show that collectivism increases face concern, which escalates online social anxiety. Face concern mediates completely between collectivism and online social anxiety, creating a serial mediation effect between face concern, online social anxiety, and lurking behavior. Trait mindfulness found to negatively modulate the pathways from collectivism to face concern and from online social anxiety to lurking. Findings highlight how traditional Chinese culture influences contemporary students' online behavior, offering a new perspective to understand social media lurking in an Eastern context, and suggest a mindfulness-based approach to mitigate associated silence and anxiety.